Efeito diferencial do gene opaco-2 sobre os teores de proteína e de lisina nas metades superior e inferior do endosperma do milho - M Barbosa, Hélio; Sant’Anna, Renato (Revista Ceres, 2025)
The protein and lysine content of the upper and lower halves of the endosperm were determined for 10 inbred lines of normal endosperm and their respective opaque-2 versions. Protein and lysine content of the germ were also determined for nine of those inbred pairs.